Maternal Hypothyroidism during Pregnancy and the Risk of Pediatric Endocrine Morbidity in the Offspring - Eshkoli, Tamar; Wainstock, Tamar; Sheiner, Eyal; Beharier, Ofer; Fraenkel, Merav; Walfisch, Asnat (American Journal of Perinatology, 2019)
Objective Previous studies suggested maternal hypothyroidism during pregnancy to be associated with cognitive impairment of the offspring. Scarce data exist regarding long-term endocrine health of the offspring. This study was aimed to assess whether children born to mothers with hypothyroidism during pregnancy are at an increased risk for long-term endocrine morbidity.Study Design A retrospective population-based cohort study compared long-term endocrine morbidity of children born between the years 1991 and 2014 to mothers with and without hypothyroidism. Multiple gestations, fetuses with congenital malformations, and women lacking prenatal care were excluded. Hospitalizations of the offspring up to the age of 18 years involving endocrine morbidity were evaluated according to a predefined set of ICD-9 codes. Kaplan–Meier's survival curves were used to compare the cumulative risk and a Cox multivariable model was used to adjust for confounders.Results During the study period, 217,910 deliveries met the inclusion criteria; 1.1% of which were with maternal hypothyroidism (n = 2,403). During the follow-up period, the cumulative incidence of endocrine morbidity among children born to mothers with hypothyroidism was 27 per 1,000 person-years and 0.47 per 1,000 person-years in the comparison group (relative risk: 2.14; 95% confidence interval [CI]: 1.21–3.79). The Kaplan–Meier's survival curve demonstrated a significantly higher cumulative endocrine morbidity in children born to mothers with hypothyroidism (log-rank test, p = 0.007). In the Cox regression model controlled for maternal age, birth weight, preterm birth, maternal diabetes, hypertensive disorders of pregnancy, induction of labor, and mode of delivery, maternal hypothyroidism was found to be independently associated with pediatric endocrine morbidity in the offspring (adjusted hazard ratio = 1.92, 95% CI: 1.08–3.4, p = 0.025).Conclusion Maternal hypothyroidism appears to be independently associated with long-term pediatric endocrine morbidity of the offspring.
Keywords: offspring; hypothyroidism; endocrine; pregnancy